Coasts, marine structures and breakwaters 2023 : resilience and adaptability in a changing climate - Burgess, Kevin (Conference proceedings, 2024)
The ICE Coasts, Maritime Structures and Breakwaters conference series, sponsored by the ICE for the past forty years, is the leading international forum for the presentation of the latest developments in coastal and maritime engineering. Since 1982, Breakwaters authors, speakers and delegates have shaped the marine engineering sector, unveiling innovative technologies, assessing techniques, making formal recommendations, demonstrating best practice, and providing in-depth technical analyses. The 2023 ICE Coasts, Marine Structures and Breakwaters conference was hosted in Portsmouth on 25-27 April 2023. Across the three days, it was attended by over 300 delegates and saw over 100 papers presented. The topics for 2023 focused on how resilience and adaptability are being addressed by the maritime sector, and covered the full spectrum of research and study, design, construction and operations. The papers presented here cover a diverse range of topics including: climate change adaptation and mitigation, sustainability and decarbonisation; construction in ports; working in marine environments; challenges of coastal engineering; coastal developments; breakwater armour; ecological aspects of design; developments in overtopping; storm and wave impact on structures; learning from historical structures and breakwaters; modular design and construction; flood risk management; numerical modelling methods; standards and Eurocodes. With contributions from those in industry and academia and featuring a wide range of international case studies, these proceedings offer an essential reference for coastal engineers and professionals.